Aerobic Dehydrogenative Coupling of Naphthols and Phenols with a Ru(OH)x/Al2O3 Catalyst under Continuous‐Flow Conditions. Issue 38 (7th October 2021) - Masuda, Koichiro; Chen, Wenlong; Hayashi, Kazushi; Shimada, Shigeru; Onozawa, Shun‐ya; Koumura, Nagatoshi; Sato, Kazuhiko; Kobayashi, Shū
Abstract: Dehydrogenative coupling reactions of naphthols and phenols were achieved with a heterogeneous catalyst, alumina‐supported ruthenium hydroxide (Ru(OH)x /Al2 O3 ), using continuous‐flow conditions and aerobic oxygen as the sole oxidant. The reactions were operated continuously for more than 16 h with good reactivity and selectivity. The Ru catalyst could be recycled at least three times by a simple online washing/activation procedure without depackaging the catalyst cartridge. The reaction provided binaphthols and biphenols as valuable products for synthetic purpose and functional materials, while an over‐oxidized quinone was obtained with 2, 6‐Di‐ tert ‐butylphenol; combining this reaction with catalytic hydrogenation under continuous‐flow conditions enabled smooth conversion of quinone to the 4, 4′‐biphenol derivative, which is a member of an important class of compounds for liquid crystals, engineering plastics, and other functional materials. Abstract : Dehydrogenative coupling reactions of phenols and naphthols were achieved under continuous flow conditions using heterogeneous Ru catalyst. The reaction employs aerobic oxygen as the sole oxidant, to realize the process clean and environment friendly. 2‐step oxidation‐hydrogenation continuous flow reactions and catalyst recycle study were shown for the efficient synthesis of biphenol compounds.